'UMP had winning streak last year' - UMP, . (Penerbit, Percetakan New Straits Times., 2014)
KUANTAN: Focusing on research, creativity and inovation has enabled Universiti Malaysia Pahang (UMP) to excel, with its researchers winning more than 80 awards in local and international competitions last year.